An Alchemist's Laboratory (1700)
A bearded alchemist sits in the midst of a bustling workshop, tending a small brazier of coals with a hand-bellows. Objects for metalworking- including an anvil, crucible, furnace and hammer- are joined by vessels for distillation and small apothecary jars with cloth lids. In the background, eight assistants or apprentices work to mix and grind materials, tend fires, and perform examinations. The hanging stuffed iguana and animal skulls indicate the alchemist's familiarity with the workings of nature, yet the skulls also act as "vanitas" or vanity objects which remind the viewer of life's passing.
Keywords: Animals--Symbolic aspects; Teniers, David, 1610-1690; Alchemists; Alchemy; Alchemy in art; Symbolism in art